A Model of Student Learning : A Cross-Disciplinary Examination of Student Reflections of Service-Learning Experiences - Goodman , Elizabeth; Westover, Jonathan; Workman , Letty; Andrade , Maureen (Experiential Learning and Teaching in Higher Education, 2022)
The purpose of this study was to measure and analyze student service and engaged learning outcomes employing the qualitative tradition of phenomenology. This study was based on the “Five R” service and engaged learning framework. The population for this project included 565 students enrolled in sixteen different course sections (eight distinct classes) taught by twelve faculty members across six academic departments in three colleges/schools on the campus of a regional teaching university in the Intermountain West. The results yielded support for each “R” in the framework (reciprocity, reflection, rewards of synergy, responsibility, and reality), thereby supporting the validity of the framework across disciplines.